The Textual Base for Modern Translations of the Old Testament - Schäfer, Rolf (Review and expositor, 2011)
This article discusses the history of scholarly texts of the Hebrew Bible up to the Biblia Hebraica Quinta, which is currently being published in individual fascicles at the rate of one or two volumes a year. It also helps the reader understand why translations of the Bible in English are sometimes so different even though the translators almost always base their work on the Hebrew Masoretic Text.